An ultra-broadband terahertz metamaterial coherent absorber using multilayer electric ring resonator structures based on anti-reflection coating. Issue 17 (23rd April 2020) - Du, Chao; Zhou, Di; Guo, Huan-Huan; Pang, Yong-Qiang; Shi, Hong-Yu; Liu, Wen-Feng; Su, Jin-Zhan; Singh, Charanjeet; Trukhanov, Sergei; Trukhanov, Alex; Panina, Larissa; Xu, Zhuo
Abstract : We propose a method for achieving THz ultra-broadband coherent absorption using the anti-reflection theory of metamaterials. Abstract : We propose a method for achieving THz ultra-broadband coherent absorption using the anti-reflection theory of metamaterials. The metamaterial absorber consists of a periodic array of electric ring resonators with a multilayered structure which form the desired refractive index dispersion and provide continuous anti-reflection over a wide frequency range. The destructive interference mechanism and resonance absorption of the absorber are determined by simulation analysis and numerical simulation. Simulation results show that the absorption bandwidth is almost 8.02 THz (absorption rate >90%) over the entire terahertz band (0.1 THz–10 THz). This design provides an effective and viable method for constructing broadband absorbers for stealth technology and the construction of enhanced transmittance devices.